Identification of natural product stereochemistry via calculation of ECD spectra - Lolli, Riccardo (Department of Chemistry, 2019)
Most commercially available antibiotics are obtained from natural products, secondary metabolites of bacteria or other living organisms. Due to the importance of this class of compounds in medicinal chemistry and growing drug resistance, efforts to discover, characterize and isolate new or improved antibiotics are continually increasing. The assignment of the absolute configuration (AC) adopted by these compounds is a crucial aspect of the characterization step and knowledge of the stereochemistry is an important factor in deciphering the interaction of these compounds with the organism and thus, the mechanism of action. In order to assign the AC, several techniques, such as X-ray diffraction and NMR experiments as well as the standard electronic spectroscopy experiments (UV-Vis, ECD, etc.) or less widespread vibrational and rotational spectroscopy experiments (VCD, ROA, etc.) can be used, often in combination. However, sophisticated synthetic strategies or difficult isolation of the natural compound often leads to a small amount of product available, making some of the previous techniques unpractical; in addition to the potential structural complexity of the molecule, this can make the experimental assignment of the AC problematic. For this reason, a computational approach, aimed at calculating observable properties of the products, generating spectra and assigning the AC through comparison between the calculated and the experimental spectra, has proven useful in many cases. Formicamycin is a natural product, isolated from a new member of Streptomyces bacteria, which has shown great activity against pathogenic drug-resistant bacteria and fungi, without developing antimicrobial resistance. This dissertation shows that the chiral axis of Formicamycin can be assigned as R, through the calculation of electronic circular dichroism (ECD) spectra and comparison to the experimentally determined spectrum in methanol. ECD spectroscopy is very sensitive to the chiral environment of chromophores and can be used to distinguish between different isomers. The computational procedure has been broadly defined in previous studies and involves three general steps: 1) generation of an ensemble of structures, 2) optimization of the structures and calculation of the rotational strengths of each and 3) generation of the Boltzmannweighted spectrum. Here, two different force fields (OPLS3 and MMFFs) were used for generating the ensemble of conformers, followed by PBE0 DFT calculations to determine the optimal geometry and finally, TDDFT calculations to compute the rotational strengths of each conformer. Furthermore, the spectra were calculated in four different solvents, using the implicit SMD method, in order to inform future studies about “variable solvent circular dichroism”. Different conformations of a molecule can be controlled by the choice of solvent and it is hypothesised that a change in solvent will result in a “fingerprint” shift in the ECD spectra that could permit assignment of the stereochemistry. The entire process was automated using a module written in Python.